(untitled) (ModaPalavra e-periódico, 2010)
Trousseau preparation has always been associated with the social role of woman and with a ritual of knowledge and values transmission. Woman trousseau for marriage has undergone modifications which have followed the historical changes in marriage itself, the feminine condition and the development of a consumption society which is strongly industrialized. The present research involved a bibliographical study, a documentary search, internet consult as well as an interview with five women from different generations. The way to preparing trousseau has undergone deep changes. In the past the trousseau was made of handcraft products which were prepared in a context of transmission of experience and values among women. It had a symbolic meaning of a gift. Today trousseau preparation is a consumption practice co-coordinated by specialized companies and guided by values established by the market. It constitutes a homewear merchandising.